Configuração do campo da educação no Brasil : estudo bibliométrico da Revista Brasileira de Educação e da Revista Brasileira de História da Educação - Silva, Márcia Regina da (2008)
This research aimed a study on the configuration of the field of Brazilian Education through publication in scientific journals in the area. From a theoretical- methodological point of view the research supported in the bibliometric approach to the analysis of scientific production. To facilitate the search, is elected as a source of data two periodicals: Revista Brasileira de História da Educação (RBHE) of the Sociedade Brasileira de História da Educação (SBHE) and Revista Brasileira de Educação (RBE), the Associação Nacional de Pós-Graduação e Pesquisa em Educação (ANPEd). The survey was developed in five parts: 1) Construction of theoretical reference: research in Education and History Education in Brazil, science, science communication, evaluation and analysis of scientific production of citations; 2) Data collection: the sample consisted of 15 numbers of each magazine, totaling 241 articles; 3) Construction of bibliometric indicators; 4) description and categorization of data collected using automated tools (software Vantage Point) for the analysis of scientific papers, seeking the organization of results for subsequent analysis and interpretation; 5) analysis and interpretation of results, carried out in the light of theoretical reference for Education and bibliometric approach. Among the partial results obtained it was found that the behavior of publication of the researchers who publish in RBHE is similar to that researchers who publish in RBE. This allows infer that the scientific production of the History of Education has particularities, however, brings in its core characteristics of research in human sciences in general, for example, high levels of individual publication, predilection for publications in books and chapters of books, high frequency of scientific communication on national sources, among others characteristics.